Retrograde Technicity and the Cinematic Avant-Garde: Towards a New Dispositif of Production - Jutz, Gabriele (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2011)
Taking as a point of departure the 1970s concept of the ‘dispositif’, this article seeks to redefine it in the context of experimental cinematic practices which reject the usual tools of filmmaking, or, more precisely, replace them by ‘retrograde’ technical means (such as handmade techniques, camera-less films, etc.). Instead of adhering to the classical notion of dispositif, which privileges the screening situation, the author rather suggest that we envisage a dispositif of production, involving the spatial relationship between the body of the artist, the ‘pro-filmic’ event and his/her material at the very moment of production, and that informs the practices of cinematic retrograde technicity.